Effect of water to cement ratio and replacement percentage of recycled concrete aggregate on the concrete strength - F., S. Khalid; Z., Zaki; S., M. Saadin; S., Shahidan (Science & Engineering Research Support Society (SERSC), 2020)
Fine Recycled Concrete Aggregate (FRCA) is one of the construction waste can be recycled. It can be the aggregate to replace the natural aggregate in concrete since we know the physical properties of materials are hard and strong. Demand for sand in the concrete production has been increased which become the problems in the concrete industry. This work deals with the effect of concrete incorporating with FRCA as partial replacement of sand. The percentage of natural sand replaced by the FRCA was 0%, 15%, 20%, 25%, 30%, 45% and 60%. Other than that, water cement ratio was manipulated variable started form 0.40, 0.45, 0.50, 0.55 and 0.60. In short, 20% replacement was the most suitable interaction of FRCA in the concrete occur that contribute to increasing in compressive strength. The porosity properties of FRCA been neutralized on that replacement percentage by the present of optimum filler effect generated form the very fine FRCA particle during the mixing process. Meanwhile, 0.50 water cement ratio was optimum condition for cement hydration process using FRCA as partial sand replacement.